Outcomes Of Chimney Technique For Aortic Arch Diseases: A Single-Center Experience With 226 Cases - Huang W (Dove Medical Press, 2019)
Wenhui Huang,1,2,* Huanyu Ding,2,* Minchun Jiang,3,* Yuan Liu,2 Cheng Huang,2 Xinyue Yang,2,4,5 Ruixin Fan,6 Jianfang Luo,2,4,5 Zhisheng Jiang1 1Institute of Cardiovascular Disease and Key Laboratory for Arteriosclerology of Hunan Province, Hengyang Medical School, University of South China, Hengyang, Hunan, People’s Republic of China; 2Department of Cardiology, Vascular Center, Guangdong Cardiovascular Institute, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong, People’s Republic of China; 3School of Biomedical Sciences, The Chinese University of Hong Kong, Sha Tin, Hong Kong, People’s Republic of China; 4Guangdong Provincial People’s Hospital affiliated to South China University of Technology, Guangzhou, Guangdong, People’s Republic of China; 5School of Medicine, South China University of Technology, Guangzhou, Guangdong, People’s Republic of China; 6Department of Cardiovascular Surgery, Vascular Center, Guangdong Cardiovascular Institute, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhisheng JiangInstitute of Cardiovascular Disease and Key Laboratory for Arteriosclerology of Hunan Province, Hengyang Medical School, University of South China, Hengyang, Hunan, People’s Republic of ChinaEmail drzhishengjiang@126.comPurpose: The goal of present study is to document our single-center experience with chimney technique for aortic arch diseases.Patients and methods: From August 2012 to October 2017, 226 patients (mean age 54±12 years; 197 men) with aortic arch diseases underwent thoracic endovascular aortic repair combined with chimney stents. The aortic stent-grafts were deployed in zone 0 (n=22), zone 1 (n=13), or zone 2 (n=191).Results: The technical success rate was 84% (189/226) and immediate type Ia endoleak (ELIa) happened in 37 (16%) patients. The 30-day mortality and morbidity rates were 2% (4/226) and 4% (8/226), respectively. Major adverse events include four major strokes, three spinal cord ischemia and one aortic rupture in the early-term. The clinical and imaging follow-up rates were 98% (218/222) and 78% (173/222), respectively. The average lengths of clinical and imaging follow-up were 22±16 months and 20±15 months, respectively. Chimney stent obstructions in left subclavian arteries were recorded in six (3%) patients. During follow-up, five patients died (2%) and two major strokes occurred (1%). One patient (0.5%) underwent reintervention.Conclusion: The current study documented that the chimney technique is effective and safe for treating aortic arch diseases in different aortic zones. Cautions are needed to assess the permanency of chimney stent and to reduce the immediate ELIa rate.Keywords: aortic arch disease, chimney, endoleak, thoracic endovascular aortic repair